Retinol and α-Tocopherol Levels in the Serum and Subcutaneous Adipose Tissue of Newly Diagnosed Basal Cell Carcinoma Patients - Ehsan GHAEDI; Fatemeh RAHROVANI; Mohammad Hassan JAVANBAKHT; Amir-Hooshang EHSANI; Ali ESRAFILI; Hamed MOHAMMADI; Mahnaz ZAREI; Mahmoud DJALALI (Tehran University of Medical Sciences, 2019)
Background: Nonmelanoma skin cancers are the most frequently occurring skin cancers. Vitamin A is involved in epithelial cell differentiation and may control skin tumor development. Vitamin E is a powerful lipophilic antioxidant that can quench and scavenge reactive oxygen species. However, there is little consistent evidence considering micronutrients and the development of basal cell carcinoma (BCC). Therefore, we aimed to investigate the possible difference between retinol and α-tocopherol in BCC patients and controls in Iranian population. Methods: This case-control study was conducted on adults with newly diagnosed BCC referred to Razi Hospital, Tehran, Iran in 2015. Serum and subcutaneous fat tissue retinol and α-tochopherol were measured by HPLC method. Results: Overall, serum retinol level was lower significantly in BCC patients (0.237±0.01 µg/ml) in comparison with control group (0.27±0.02 µg/ml, P-value: 0.038). However serum ɑ-tocopherol level was not significantly different between BCC patients (4.41±0.33 µg/ml) and control subjects (4.06±0.35 µg/ml, P-value=0.18). Subcutaneous adipose tissue retinol was lower significantly in BCC patients (38.60±3.30 ng/mg) compared with control group (54.78±3.49 ng/mg, P-value=0.002). Furthermore, results revealed lower subcutaneous adipose tissue ɑ-tocopherol in BCC patients (4.41±0.33 µg/ml) in comparison with control group (4.06±0.35 µg/ml, P-value=0.18). Conclusion: Skin tissue concentration of retinol and ɑ-tocopherol and serum retinol level was lower in BCC patients in comparison with control group but serum ɑ-tocopherol was not different between groups.